2003
DOI: 10.1515/bc.2003.002
|View full text |Cite
|
Sign up to set email alerts
|

3’UTRs of Glutathione Peroxidases Differentially Affect Selenium-Dependent mRNA Stability and Selenocysteine Incorporation Efficiency

Abstract: Selenoprotein mRNAs are particular in several aspects. They contain a specific secondary structure in their 3'UTR, called Secis (selenocysteine inserting sequence), which is indispensable for selenocysteine incorporation, and they are degraded under selenium-limiting conditions according to their ranking in the hierarchy of selenoproteins. In the familiy of selenium-dependent glutathione peroxidases (GPx) the ranking is GI-GPx > or = PHGPx > cGPx = pGPx. This phenomenon was studied by mutually combining the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 43 publications
1
51
0
1
Order By: Relevance
“…Post-transcriptional mechanisms conferred by the 39-untranslated region that contains the selenocysteine insertion sequence have been studied in more detail. This sequence element is involved in the co-translational incorporation of selenocysteine into the nascent polypeptide chain (Copeland et al, 2000(Copeland et al, , 2001) and seems to be essential but not exclusive in the regulation of mRNA stability in the case of selenium deficiency (Brigelius-Flohe, 1999;Muller et al, 2003).…”
Section: Molecular Mechanisms Of Gpx4 Transcription Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-transcriptional mechanisms conferred by the 39-untranslated region that contains the selenocysteine insertion sequence have been studied in more detail. This sequence element is involved in the co-translational incorporation of selenocysteine into the nascent polypeptide chain (Copeland et al, 2000(Copeland et al, , 2001) and seems to be essential but not exclusive in the regulation of mRNA stability in the case of selenium deficiency (Brigelius-Flohe, 1999;Muller et al, 2003).…”
Section: Molecular Mechanisms Of Gpx4 Transcription Regulationmentioning
confidence: 99%
“…This peculiarity of selenoprotein biology suggests that high-ranking selenoproteins may play a more essential role in the organism (Novoselov et al, 2005). Although the underlying mechanism of selenoprotein expression hierarchy is not fully elucidated, mRNA stability has been proposed as a regulation level (Weiss-Sachdev and Sunde, 2001;Muller et al, 2003). In the case of the low-ranking GPx1 it has been shown that nonsense-mediated decay causes degradation of the mRNA molecule under selenium deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of a specific hairpin structure in the 3Ј untranslated region (3ЈUTR) of the mRNA, the so called selenocysteine insertion sequence (SECIS), as well as specific SECIS-binding proteins, the Secspecific elongation factor (eEFSec) and the Sec-tRNA Sec , UGA is recognized as a UGA-Sec codon rather than as a stop codon (reviewed by Krol, 2002). As SECIS we inserted the 3ЈUTR of the selenium-dependent glutathione peroxidase PHGPx into the 3ЈUTR of the CD21 expression construct E. This SECIS element was chosen because it is reported to exhibit a high Sec incorporation efficiency than the SECIS elements of other glutathione peroxidases (Muller et al, 2003). In order to generate a CD21 protein with a constitutively open bridge between cys-2 and cys-4, the same cysteines were mutated to methionine (CD21-Met) (construct G, Fig.…”
Section: Cd21 Shedding Depends On Scr16mentioning
confidence: 99%
“…In a second mutagenesis round the cysteine codons of Cys941 and Cys968 were replaced by the selenocysteine codon UGA using primers Tg219 (5Ј-GCTGTTGTAACTCTGGAGTGAGAAGATGGGTATATGC-3Ј) for cys-2 and Tg223 (5Ј-CCTCCCCTGGCGGTTTGAAGATCCAGATCTCG-3Ј) for cys-4. The selenocysteine-insertion-sequence (SECIS) of the selenium-dependent glutathione peroxidase PHGPx (Muller et al, 2003) was amplified by PCR from 293 cDNA using primers Tg224 (5Ј-TTGACGTCGACGCTCCACAAGTGTGTGG-3Ј) and Tg225 (5Ј-GGTACCGTCGACGTCTGTTTATTCCCACAAGGTA-3Ј) and inserted via a SalI site 3Ј to the UAG stop codon. Cysteines were changed to methionines (construct G) using primers Tg218 (5Ј-GCTGTTGTAACTCTGGAGATGGAAG- Subsequently, a serine protease is activated that is necessary to activate the metalloprotease involved in CD21 shedding.…”
Section: Site Directed Mutagenesis Of Disulfide Bridges Within Scr16mentioning
confidence: 99%
“…Others appear to be of less vital importance and become only poorly synthesized when the Se supply is limiting (5). The circulating extracellular GPx3 and the ubiquitous cytosolic GPx1 belong to these unprivileged selenoproteins (6). Their expression declines markedly when Se is limiting, and therefore they can be used to assess the Se status of individuals.…”
Section: Introductionmentioning
confidence: 99%